2010
DOI: 10.1063/1.3275868
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation characteristics of yttria-doped zirconia in the nanosecond and femtosecond regimes

Abstract: The laser ablation characteristics of yttria-stabilized zirconia ͑YSZ͒ have been investigated as a function of the target microstructure and dopant level for different nanosecond-͓ArF, KrF, and XeCl excimers; Nd:YAG ͑yttrium aluminum garnet͒ ͑fourth harmonic͔͒ and femtosecond-laser sources ͓Ti:sapphire ͑fundamental and third harmonic͔͒. Particle ejection, which compromises the quality of coatings prepared by pulsed laser deposition ͑PLD͒, was analyzed in detail. Nanosecond-laser pulses cause a severe thermomec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 48 publications
(55 reference statements)
3
40
0
Order By: Relevance
“…[5][6][7][8][9][10] Plant leaves, especially green leaves, are common landscaping and agricultural materials and lasers could be creatively used for many possible innovative applications. Plant leaves exhibit very complicated optical properties because they have complex multilayer structures and are basically a composite of many dissimilar optical elements, including photosynthesizing pigments.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] Plant leaves, especially green leaves, are common landscaping and agricultural materials and lasers could be creatively used for many possible innovative applications. Plant leaves exhibit very complicated optical properties because they have complex multilayer structures and are basically a composite of many dissimilar optical elements, including photosynthesizing pigments.…”
mentioning
confidence: 99%
“…Figure 10a, b shows an increasing trend of refractive index (n) with increase up to 6 wt% for basic and 8 wt% for acidic Fe 3 O 4 dopant concentrations. However, decrease in refractive index with further increase in dopant concentration might be because of the incorporation of more oxygen vacancies in zirconia lattice which produce stabilization in zirconia [21]. This stabilization was observed in the XRD data (Fig.…”
Section: Introductionmentioning
confidence: 59%
“…Thin films of metal oxide doped zirconia have been prepared by laser ablation [21], RF sputtering [22,23] and sol-gel [24] etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of zirconia phase in the microstructure of zirconia mullites affects the quality of the product. It is observed that stable monoclinic zirconia phase is present below 1,170 C, whereas the transformation temperature of monoclinic zirconia to pure tetragonal zirconia is 1,170 C, which remains stable up to the temperature of 2,370 C [5]. The transformation temperature from tetragonal zirconia to cubic zirconia is 2,370 C [5].…”
Section: Introductionmentioning
confidence: 86%